O TRABALHO PEDAGÓGICO COM A MÚSICA EM UMA PRÉ-ESCOLA DO MUNICÍPIO DE BREVES-PA - MENEZES, Elayne Guimarães Dias (2024)
This Course Conclusion Paper aims to identify the favorable aspects that music, as a pedagogical tool, can provide in the teaching-learning process implemented in a preschool. Based on theoretical sources and experience reports of early childhood education professionals, this research proposed to answer the following main question: "How is music used in pedagogical practices in the daily life of a preschool in the city of Breves-PA?" For its implementation, a qualitative approach was used, based on data collected through the application of questionnaires and research in theoretical productions that support the guiding questions of the study. The questionnaires were applied to 07 (seven) teachers who work in a kindergarten school (Pre-school), located in the urban area of the city of Breves-PA. Thinking about music and its contributions, we concluded in this regard that this tool, in addition to helping the development of various abilities in cognitive, motor and linguistic aspects, helps in the process of socialization of children, in learning content and in living in harmony with each other.